The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/pde.13788
|View full text |Cite
|
Sign up to set email alerts
|

A barrier to care: Distance traveled affects adherence to treatment and follow‐up plans for patients with infantile hemangioma

Abstract: A chart review was performed of all patients diagnosed with infantile hemangioma in the pediatric dermatology clinic to determine whether distance traveled by the patient affected adherence to follow-up and treatment plans. An increase in distance was associated with an increase in likelihood of nonadherence to treatment or follow-up plans. Compared to patients who lived within 10 miles of a pediatric dermatologist, families who lived farther away were less likely to adhere to treatment plans. Families who tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Given that poor access to dermatologists can lead to delays in care and worse dermatologic disease outcomes, it is critical to improve patients' access to pediatric dermatologists 7,8,25 . Therefore, while the SPD continues to develop and implement strategies to increase the pediatric dermatology workforce, efforts should also be made to improve the distribution of the current workforce.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that poor access to dermatologists can lead to delays in care and worse dermatologic disease outcomes, it is critical to improve patients' access to pediatric dermatologists 7,8,25 . Therefore, while the SPD continues to develop and implement strategies to increase the pediatric dermatology workforce, efforts should also be made to improve the distribution of the current workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Given that poor access to dermatologists can lead to delays in care and worse dermatologic disease outcomes, it is critical to improve patients' access to pediatric dermatologists. 7,8,25 Jennifer T. Huang https://orcid.org/0000-0001-6191-7486…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to dermatologist shortages in rural areas, studies have shown that rural residents travel longer distances to see specialists, experience longer wait times, and suffer higher mortality rates from melanoma and Merkel cell carcinoma compared with urban residents [1][2][3][4]. In turn, longer travel distances to dermatologists lead to decreased treatment adherence and higher non-attendance rates [5]. Recent data have highlighted that younger dermatologists are increasingly practicing in urban settings, suggesting that the urban-rural workforce gap will continue to widen if strategies to recruit rural dermatologists are not implemented [1].…”
Section: Introductionmentioning
confidence: 99%